2020
DOI: 10.5758/vsi.200018
|View full text |Cite
|
Sign up to set email alerts
|

Standard or Variant Meso-Rex Shunts for Children with Variceal Bleeding due to Extrahepatic Portal Vein Obstruction: A Report of Two Cases

Abstract: Extrahepatic portal vein obstruction (EHPVO) is the most common cause of pediatric portal hypertension and can cause life-threatening variceal bleeding. Meso-Rex shunt (MRS) is a surgical procedure that restores physiological portal venous blood flow to the liver by using a graft to connect the superior mesenteric vein and the left portal vein within the Rex recess, and can relieve variceal bleeding and other complications associated with EHPVO. Although the MRS is regarded as an optimal and potentially curati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…The pullout route, on the other hand, required dissection of the confluence of the SMV and SV behind the pancreas. The bypass vessel in the conventional pullout route was located behind the pancreas (R2) but was most difficult to be dissected in PVCT [ 21 ]. But in some patients, the retrogastric route (R1) could be used instead of dissecting the retropancreatic tunnel.…”
Section: Discussionmentioning
confidence: 99%
“…The pullout route, on the other hand, required dissection of the confluence of the SMV and SV behind the pancreas. The bypass vessel in the conventional pullout route was located behind the pancreas (R2) but was most difficult to be dissected in PVCT [ 21 ]. But in some patients, the retrogastric route (R1) could be used instead of dissecting the retropancreatic tunnel.…”
Section: Discussionmentioning
confidence: 99%
“…Oh et al [ 5 ] reported 2 cases of meso-Rex shunt in children with extrahepatic portal vein occlusion. One case was successful, and the other failed; the reason for the different outcomes was obscure.…”
Section: ) Be Courageous To Report a Nightmare Casementioning
confidence: 99%
“…Modified Meso-Rex Shunt for Extrahepatic Portal Vein Obstruction and Variceal Bleeding after Pancreatoduodenectomy in an Adult www.vsijournal.org LPV, suitable mesenteric venous inflow, and an adequate autologous conduit [2]. Therefore, preoperative imaging evaluation and meticulous operative techniques determine the success of surgery.…”
Section: Image Of Vascular Surgerymentioning
confidence: 99%
“…Meso-Rex shunt (MRS) is an attractive treatment for EHPVO, which involves shunting the mesenteric vein to the intrahepatic left portal vein (LPV) within the Rex recess using an autologous vein graft. MRS is the best option for children because it can perfuse the liver to allow for growth [ 2 ]. EHPVO may develop after pancreatoduodenectomy (PD) and cause VB at the hepaticojejunostomy (HJ) site.…”
mentioning
confidence: 99%
See 1 more Smart Citation